SOSIALISASI PEMBUATAN HANDSANITIZER SERAI WANGI DI KELURAHAN BATU URIB KECAMATAN LUBUKLINGGAU UTARA II KOTA LUBUKLINGGAU - Yeni Trianah (LP4MK STKIP PGRI Lubuklinggau, 2019)
This activity aims to provide socialization and training to the people of Batu Urip village in making hand sanitizer by utilizing citronella in the city of Lubuklinggau. This activity was carried out from September to October 2019 which included socialization, training, coaching, and evaluation. This activity was attended by 23 participants from PKK, Batu Urip sub-district, North Lubuklinggau II. The socialization provided included the benefits of citronella as a basic ingredient for making hand sanitizer, the activity continued with a demonstration of making hand sanitizer. Then continued with training on making hand sanitizer from citronella. Based on the results of community service implementation activities, there is an increase in community skills through observation in terms of material selection, manufacturing process, and product results, namely from 41.67 (initial skill value) to 91.67 (final skill value).